Education and Alcohol Consumption among Older Americans; Black–White Differences - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Public Health, 2016)
Abstract: Purpose: Although the link between education and alcohol consumption is known, limited information exists on racial differences in this link. We conducted the current study to test Black- White differences in the association between education and alcohol consumption among older adults in the United States. Methods: This cross-sectional survey enrolled 1,493 Black (n=734) and White (n=759) older adults (age 66 or more) in United States. Data came from the Religion, Aging, and Health Survey, 2001. Race, demographics, socio-economics, and alcohol consumption were measured. Independent variable was education level. Outcome was alcohol consumption. Race was the focal moderator. Logistic regression was used for data analysis. Results: Education was positively associated with ever drinking in the pooled sample. Race, however, interacted with education level on drinking, suggesting a smaller effect of education on drinking for Blacks compared to Whites. Among Whites, high school graduation and college graduation were associated with increased odds of ever drinking, net of covariates. Among Blacks, high school graduation but not college graduation was associated with ever drinking. Conclusion: Blacks and Whites differ in how socio-economic status (i.e. education) shapes behaviors health behaviors (i.e. drinking). How race modifies consequences and correlates of social determinants of health is not yet clear. College graduation may result in the same level of change to the social network and income of race group members. Lower effect of education on health of Blacks may be due to the structural role of race and racism that has resulted in lower job availability and pay for Blacks.